2011
DOI: 10.1002/bmc.1707
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of aconitine in rat skin after oral and transdermal gel administrations

Abstract: The purpose of this study was to evaluate percutaneous penetration and arrhythmogenic effects of aconitine after transdermal administration, compared with the oral route. Skin penetration of aconitine was tested by a microdialysis technique in rats and in vivo recovery was determined by retrodialysis. After oral and transdermal administration of aconitine, dialysate was sampled at 20 min intervals until the end of the experiment for the determination of concentration of aconitine in skin. Blood samples were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Transdermal permeation experiments using live murine subjects were performed for comparative purposes against ex Vivo data. Solutions of aconitine and STX-ge in either ethanol or DMSO were applied to the shaved back of male Sprague–Dawley rats under general anesthesia (see Supporting Information for experimental details) . The animals were sacrificed, their skin removed, sectioned, and analyzed following the same experimental procedures used for ex vivo experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transdermal permeation experiments using live murine subjects were performed for comparative purposes against ex Vivo data. Solutions of aconitine and STX-ge in either ethanol or DMSO were applied to the shaved back of male Sprague–Dawley rats under general anesthesia (see Supporting Information for experimental details) . The animals were sacrificed, their skin removed, sectioned, and analyzed following the same experimental procedures used for ex vivo experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Solutions of aconitine and STX-ge in either ethanol or DMSO were applied to the shaved back of male Sprague−Dawley rats under general anesthesia (see Supporting Information for experimental details). 28 The animals were sacrificed, their skin removed, sectioned, and analyzed following the same experimental procedures used for ex vivo experiments. Pathologic evaluation of the tissue sections revealed that in all samples analyzed, besides skin epidermis, dermis, and hypodermis layers, muscle tissue was also present.…”
Section: Desi-ms Ion Imagesmentioning
confidence: 99%
“…There have been more and more reports on efficacy of transdermal patch in treating both human and animal diseases (Plosker, 2011;Zhang et al, 2011;Dou et al, 2011). Use of Chinese Herbal Medicine (CHM) as transdermal agents is a new combination of Traditional Chinese Medicine (TCM) with modern pharmaceutical technology (He et al, 2009;Qian et al, 2011).…”
Section: Introductionmentioning
confidence: 99%